(untitled) (Edad Media. Revista de Historia, 2026)
Philippa of Lancaster (1360–1415), eldest daughter of the second Dukes of Lancaster, married King John I of Portugal in February 1387. After the wedding, the monarch granted her a household composed of several high-ranking officials and ladies-in-waiting. Among them stood out Beatriz Gonçalves de Sousa, widow of a prominent vassal of the previous reign and head of the Coutinho lineage. In this first royal household, three of the maidens who served the queen were Beatriz’s daughters, while her eldest son assumed responsibility for one of its departments. Over the course of several reigns, this lineage maintained the same pattern: owing much of its wealth and prestige to royal favor.